The rise. 1978 - Yomtov, Nel (New York : Franklin Watts, an imprint of Scholastic Inc., 2023)
Explores the key events of the Civil Rights Movement, focusing on the year 1978, including the Supreme Court case Regents of the University of California v. Bakke, Max Robinson, and more.
Introduction: The Way It Was -- An era of groundbreakers -- The gathering crowds -- Pride and policy -- Taking it to the streets -- Victories -- A declaration for humanity -- Conclusion: The Legacy of 1978 in Civil Rights History -- Biography: Toni Morrison -- Timeline.
School Library Journal, April 2023
Includes bibliographical references (pages 92-93) and index.
8.2
5-8
1160L
Keywords: African Americans -- Civil rights -- History -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature; Civil rights workers -- United States -- Juvenile literature; African Americans -- Civil rights -- History; Civil rights movements -- History -- 20th century; Civil rights workers